2023
DOI: 10.1039/d2rp00055e
|View full text |Cite
|
Sign up to set email alerts
|

Integrating chemistry laboratory–tutorial timetabling with instructional design and the impact on learner perceptions and outcomes

Abstract: For chemistry, where learners are required to integrate experimental observations with theoretical knowledge, laboratory work appears to be a viable instructional strategy. However, research has shown that chemistry laboratory instruction often fails to live up to its potential. The scheduling practice in higher education (HE) separating theory lessons and practical work into temporally disjointed sessions could exacerbate the theory–laboratory disconnect. This paper continues an earlier work, in which integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Additionally, studies published as recently as 2022 have used the MLLI and its three proposed categories in their investigations. For example, one study reported the average scores of the cognitive, affective, and cognitive/affective categories to assist in the investigation of the differences between traditional chemistry courses and integrated lecture-lab block courses (Lau et al, 2023).…”
Section: Mlli Uses and Score Reportingmentioning
confidence: 99%
“…Additionally, studies published as recently as 2022 have used the MLLI and its three proposed categories in their investigations. For example, one study reported the average scores of the cognitive, affective, and cognitive/affective categories to assist in the investigation of the differences between traditional chemistry courses and integrated lecture-lab block courses (Lau et al, 2023).…”
Section: Mlli Uses and Score Reportingmentioning
confidence: 99%
“…10 It is known that chemistry is an intrinsically complex subject, studying the substances from a microscopic perspective, where learners need to connect experimental observations with theoretical knowledge. 11 Given that laboratory work provides an avenue to comprehend chemistry knowledge and practice chemistry investigations, 12 the consensus has been reached by the domain of chemistry education that practical science plays an indispensable part in chemical investigations. 13 Cullinane et al further pointed that chemistry education is typically characterized by laboratory work, 14 which is mainly due to the early emphasis on the experimental chemistry laid by school chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%